On a method for solving the reliability problem of the mechanical system - Pho, Nguyen Van (Vietnam Journal of Mechanics, 1988)
In this paper the problem of reliability is formulated in stochastic programming forms and corresponding algorithms are given. In some ordinary conditions of moebanical system, stochastic programming problems can change by that ones or the deterministic mathematical programming.